COLLABORATIVE GOVERNANCE IN MANAGING MARINE ECOTOURISMS: A CASE STUDY AT KLAYAR BEACH, PACITAN REGENCY, INDONESIA - M. Husni Tamrin; Wildan T. Raharja; Indra P. P. Salmon (Universitas Padjadjaran, 2023)
This study aims to analyze the collaborative governance process in ecotourism development at Klayar Beach, Pacitan. This study implies that the sustainability of the role of collaboration between the government and non-government must be carried out by looking at the aspects of building trust, and commitment, as well as understanding and mutual agreement with the sustainability goal of marine ecotourism being able to be carried out optimally. This study uses a qualitative method with a case study approach. The results showed that the dynamics of tourists visiting the Klayar Beach ecotourism destination continued to increase every year, even though there had been a decline due to the disaster. However, the government through a collaboration scheme has succeeded in rebuilding the tourism aspect through trust and commitment to development. Looking at future projections, local governments must prepare further strategies in the context of common understanding. In addition, today's progress, which has shown a positive local socio-economic impact with nature conservation that has been implemented, must be able to be maintained and continuously improved along with opportunities for increasing tourists in the future. The conclusion shows that collaboration by local government in Pacitan Regency and non-government in general has shown a positive impact, but it is necessary to pay attention to mutual understanding and agreement within the scope of harmony between implementing parties, considering challenges faced in multi-actor development. It is very complex and has the potential to become an obstacle in the process of development of Klayar Beach Ecotourism.